Spin Bias Is Common in the Abstracts and Main Body of Systematic Reviews and Meta-analyses of Hip Arthroscopy in the Setting of Borderline Hip Dysplasia - Jeffrey J. Theismann, M.D; Matthew J. Hartwell, M.D; Samuel G. Moulton, M.D; Stephanie E. Wong, M.D; Alan L. Zhang, M.D (Elsevier, 2024)
Purpose: To assess the quality and presence of spin bias in the abstracts of systematic reviews and meta-analyses that evaluated the outcomes of using hip arthroscopy for the treatment of hip pathology in the setting of borderline hip dysplasia. Methods: PubMed and Embase were searched using the terms "borderline hip dysplasia" and "systematic review" or "meta-analysis." Forty-one initial studies were identified, and 12 met the inclusion criteria. Study characteristics were then collected, and each study was evaluated for the 15 most common types of bias and study quality using A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR 2) rating system. Inclusion criteria included a systematic review with or without meta-analysis, published in a peer-reviewed journal, accessible in English, with outcomes after hip arthroscopy for borderline hip dysplasia. Results: The 12 reviewed studies were published between 2016 and 2023, and 10 of the studies represented Level IV evidence (2 studies were Level III evidence). At least 1 form of spin was identified in 83% (10/12) of the included studies. Regarding the specific categories of spin type, misleading interpretation was identified in 58% (7/12) of the studies, misleading reporting in 67% (8/12) of the studies, and inappropriate extrapolation in 50% (6/12) of the studies. On the basis of the AMSTAR 2 assessment, 92% (11/12) were categorized as either low quality or critically low quality, with 1 study being categorized as moderate. Conclusions: Spin bias is frequently encountered in the abstracts for systematic reviews and meta-analyses that evaluate outcomes after hip arthroscopy for the treatment of hip pathology in the setting of borderline hip dysplasia. Level of Evidence: Level IV, systematic review of Level III and IV studies.